A Tour Of Ibali: Digital Collections UCT Showcasing Collections for Discovery - Muftic, Sanjin (My University, 2023)
In 2021, the Digital Library Services (DLS) department at University of Cape Town Libraries launched a university-wide showcasing platform for the university's digital collections, here: https://ibali.uct.ac.za. The site is called Ibali (isiXhosa for 'story') and it runs on a set of semantic web technologies called Omeka S and IIIF. Ibali is part of the Libraries' drive to nurture an Open Access space where digital collections can be created, curated, published and showcased. It is a highly collaborative and flexible, future-thinking online repository space. Since its launch a number of diverse collections have already been showcased on Ibali - including a library of open access resources focusing on climate change, transcriptions of the early South African Black Press, and an archive on an active theatrical research project. This presentation offers a walkthrough of some of the metadata infrastructure that we have set up to ensure discoverability and interoperability, especially with regards to showcasing collections from the Global South. The use and institutional implementation of several add-on modules will be showcased to highlight how schemas and ontologies are used to provide integration between indigenous data and the semantic web.
Keywords: Digital Collections; Multilingual Support; Ibali